Giant Water Bugs, Electric Light Bugs, Lethocerus, Abedus, Belostoma (Insecta: Heteroptera: Belostomatidae) - Paul M. Choate (EDIS)
The heteropteran family Belostomatidae contains the giant water bugs. These large, predatory, aquatic insects have the largest body size among the Heteroptera. Adults of some South American species reach 4 inches in length. Individuals occur in ponds and ditches where they suspend below the surface, respiring through two abdominal appendages which act as siphons. During mating season they fly from pond to pond or pool of water. It is during these flights that these insects fly to lights in large numbers, earning their other common name, "electric light bugs". Individuals are capable of inflicting a painful bite with their strong beak, and may also pinch with their front legs. Individuals prey on aquatic insects, small fish, frogs, tadpoles, small birds, and other organisms they are able to capture. Powerful enzymes are injected into prey to kill them. Adults of Lethocerus are considered a delicacy in Asia, and are eaten both fresh and cooked. This document is EENY-301, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2003. Revised: October 2003.